Morphological study of pollen-grains for the wild species of the genus Erysimum L. (Crucifereae) in Iraq (Baghdad Science Journal, 2012)
Pollen grains morphology have been studied for the wild species of the genus Erysimum L. which belong to Crucifereae family in Iraq. These species are E. filifolium Boiss. et Hausskn., E. oleifolium J. Gay, E. repandum L., E. eginense Hausskn. ex Bornm., E. aucheranum J. Gay, E. cheiranthoides L., E. alpestre Ky. ex Boiss., E. kurdicum Boiss. et Hausskn., E. tenellum DC., E. strophades Boiss., E. gladiiferum Boiss. et Hausskn., E. nasturtioides Boiss. et Hausskn. The study was performe by using light microscope . The study reveal that there was only one type of pollen grain named Tricoplate in all studied species . The study also demonstrated that there were differences among pollen grains morphology . The species E. kurdicum , E. alpestre , and E. strophades have shown Oblate form , while the species E. oleifolium , E. repandum , E. filifolium , E. aucheranum , and E. tenellum have Oblate-spheroidal form . On the other hand the species E. eginense , E. gladiiferum , E. cheiranthoides , and E. nasturtioides have Sub-oblate pollen . It was also noticed that the outer layer of pollen grains has more thickened wall than the inner layer . The data also shown that there were differences in pollen grains sizes . The species E. oleifolium , E. strophades , E. filifolium , E. gladiiferum , E. E. kurdicum , E. aucheranum , E. tenellum , E. repandum , and E. nasturtioides have very small pollen grains , while they were small to middle in the other species .The data getting from this study showed important taxonomical characters to classifying the studied species